Sosialisasi Dan Pendampingan Penggunaan Buli Buli Panas Untuk Mengurangi Nyeri Haid Pada Remaja Di Desa Tangkil Kabupaten Bogor - Ula, Zumrotul; Mainassy, Meillisa Carlen; Fatimah, Sitti; Latif, Farida (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2024)
Menstruation is periodic bleeding from the uterus that begins approximately 14 days after ovulation periodically due to the shedding of the endometrial lining of the uterus. Dysmenorrhea is severe pain or tenderness in the lower abdomen that occurs when a woman experiences her menstrual cycle. Pain usually lasts just before menstruation, during menstruation, until the end of the menstrual cycle. Continuous pain makes the sufferer unable to move. The aim of PkM is to find out the effect of applying a warm compress to reduce the level of pain, to know the client's response to the application of a warm compress to reduce the level of pain, to know the level of reduction in joint pain after being given a warm compress, to find out whether there are complications due to applying a warm compress to reduce the level of pain. The method used by PkM activities is socialization and assistance in the use of hot bladders to reduce menstrual pain in teenagers in Tangkil Village, Bogor Regency. The results of community service were an increase in respondents' knowledge about menstrual pain and changes in the pain scale before and after assistance in providing hot bladder. The conclusion from this activity is that the knowledge of teenagers in Tangkil Village, Kab. Bogor regarding menstrual pain in teenagers improves with socialization and assistance in providing hot bladders to reduce menstrual pain and individuals can do it themselves to deal with menstrual pain.